Oral language comprehension interventions in school-age children and adolescents with developmental language disorder: A systematic scoping review. (May 2021) - Tarvainen, Sirpa; Launonen, Kaisa; Stolt, Suvi
Background & aims: Difficulties understanding spoken language are associated with several social and academic risks in school-age children and adolescents with developmental language disorder (DLD). Still, interventions for this group have received little attention, and there are no reviews focusing on oral language comprehension interventions in school-age children and adolescents. The objective of this systematic scoping review was to identify interventions targeting oral language comprehension in school-age children and adolescents with DLD. Further, the aim was to examine the focus of intervention, efficacy, and level of evidence of the identified interventions. The present review is the second part of a larger search on oral language comprehension interventions. The first review examined the same factors in children 8 years and younger. Methods: A systematic scoping review of eight databases was conducted. Of the 2399 sourced articles, 12 met the inclusion criteria. Another 8 articles were identified through reference lists of sourced articles. In these 20 articles, containing 21 studies, 1661 children aged 5–16 years participated. The data were extracted and analysed, and the intervention focus, efficacy, and level of evidence were examined. Main contribution: In the interventions intended for school-age children and adolescents with DLD, three intervention foci were identified that targeted aspects of language and language processing, as well as modifying the communicative environment. Of the included studies, 57% reported positive results, 14% reported mixed results, and 29% reported no effects on oral language comprehension. The level of evidence varied. One can have high confidence in the results of 19%, moderate in 38%, and indicative confidence in 43% of the included studies. Conclusions: Results of the present review suggest that there are a few interventions providing high confidence on the efficacy of improving oral language comprehension difficulties in school-age children and adolescents with DLD. Most interventions indicating efficacy provide moderate or indicative confidence in the results. More research with a high level of evidence is urgently needed. Most of the interventions indicating efficacy focused directly on language skills or modified the communicative environment. The results suggest that the therapy techniques focusing on improving language processing skills indicate efficacy only when they aim at compensating current language processing skills, not trying to improve them. Implications: The findings on different therapy techniques, their focus of intervention, efficacy, and level of evidence provide information for clinical practice and direct future investigations in this sparsely researched topic.